2020
DOI: 10.1002/bio.3980
|View full text |Cite
|
Sign up to set email alerts
|

Rapid biosynthesis of fluorescent CdSe QDs in Bacillus licheniformis and correlative bacterial antibiotic change assess during the process

Abstract: Cadmium selenide (CdSe) quantum dots (QDs) were biosynthesized rapidly in 18 h in Bacillus licheniformis ATCC 11946 (B. licheniformis); this process benefited from the cellular machinery of bacteria metal metabolism, in which inorganic Na2SeO3 and CdCl2 were chosen as raw materials to produce high quality CdSe QDs by a designed two‐step protocol. Research outcomes demonstrated that the purified CdSe QDs possessed maximum fluorescence intensities at weak alkalinity solutions and had good fluorescence stabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In some cases, as with reductases, the same class of protein is found to perform b i o m i n e r a l i z a t i o n a c r o s s m u l t i p l e o r g a nisms. 16,20,21,24,73,97,98,115,[117][118][119]121,122,250,[252][253][254][255][256][257][258][259]265 It is also common for peptides or proteins to mediate the synthesis of several types of materials, such as CdSe quantum dots and Se nanoparticles, or as with silicatein, native product silica as well a s t i t a n i a , g a l l i u m , c e r i u m , a n d b a r i u m o xides. 92,124,193,24,194,195,266,267 Frequently, nanomaterial biomineralization is initially observed and performed in vivo; however, the few examples of in vitro biomineralization with purified recombinant proteins often show a higher level of control over the final nanocrystal size and shape, while also providing a deeper understanding of the nanoparticle synthesis mechanism.…”
Section: Future Developments Needed For Improved Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, as with reductases, the same class of protein is found to perform b i o m i n e r a l i z a t i o n a c r o s s m u l t i p l e o r g a nisms. 16,20,21,24,73,97,98,115,[117][118][119]121,122,250,[252][253][254][255][256][257][258][259]265 It is also common for peptides or proteins to mediate the synthesis of several types of materials, such as CdSe quantum dots and Se nanoparticles, or as with silicatein, native product silica as well a s t i t a n i a , g a l l i u m , c e r i u m , a n d b a r i u m o xides. 92,124,193,24,194,195,266,267 Frequently, nanomaterial biomineralization is initially observed and performed in vivo; however, the few examples of in vitro biomineralization with purified recombinant proteins often show a higher level of control over the final nanocrystal size and shape, while also providing a deeper understanding of the nanoparticle synthesis mechanism.…”
Section: Future Developments Needed For Improved Materialsmentioning
confidence: 99%
“…Other proteins implicated in the reduction of selenite to a reactive form of Se 2– include several reductases, such as superoxide reductase and cytochrome c reductase. , In some cases, selenium reducing pathways must be carefully balanced to favor to production of CdSe over the precipitation of elemental selenium. In one example, the metal-reducing bacteria Shewanella oneidensis was applied to produce CdSe quantum dots .…”
Section: Functional Materials Produced Using Biomineralizationmentioning
confidence: 99%
“…This simple and environmentally friendly method opens the possibility to use cells to produce QDs. Other studies for the biosynthesis of Cd-based QDs in different bacterial cells have been reported (Gallardo Benavente et al, 2019;Lin et al, 2020;Sur et al, 2019).…”
Section: Cadmium-based Nir Qdsmentioning
confidence: 99%
“…The ‘space–time coupling ARLCS strategy’ was first proposed to account for the synthesis of CdSe QDs in S. cerevisiae in 2009 [ 5 , 8 , 26 , 28 , 39 , 40 ], and it has been expanded to the synthesis of various nanocrystals, such as CdTe, ZnSe, CuSe and Te nanorods, in other cell types including Staphylococcus aureus [ 41 43 ], Fusarium oxysporum [ 44 ], E. coli [ 45 ], S. oneidensis [ 11 , 15 , 46 ], Bacillus licheniformis [ 47 ], B acillus amyloliquefaciens [ 48 ], Rhodotorula mucilaginosa [ 49 ], Candida utilis [ 50 ], mammalian cells [ 51 ], Tetrahymena pyriformis [ 52 , 53 ], Caenorhabditis elegans [ 54 ] and earthworms [ 38 , 55 ], by easily altering the raw chemicals fed to the cells (Fig. 1 ).…”
Section: How To Synthesize Designer Nanocrystals In Live Cellsmentioning
confidence: 99%